The modelling and performance of training shoe cushioning systems - Thomson, R. D.; Birkbeck, A. E.; Tan, W. L.; McCafferty, L. F.; Grant, S.; Wilson, J. (Sports Engineering, 1999)
Training shoes are available with different technical features, many of which relate to the sole cushioning system. Such systems tend to fall into two classes: air-soled (AS) and non-air-soled (NAS). In the current work, finite element analyses were used to determine whether a hyperelastic constitutive equation can be used to model deformation that is consistent with physical, quasi-static, uniaxial compression tests.